A Brief Study on Face Expression Recognition System (International Journal of Innovative Research in Computer Science & Technology, 2022)
The most significant type of expressive is  body language. Nonverbal communication. Face  expression recognition (FER) systems have been  developed to serve real-world applications rather than  laboratory settings, owing to advances in hardware and  sensor technologies. FER is a technique of communicating  social information without the need of words. FER may be  utilized in a number of settings, including healthcare,  education, criminal investigation, and HMI (Human Robot  Interface) (HRI). FER systems are being utilized in a  variety of industries, including healthcare, robotics, education, and entertainment. In this article, the author  discusses Face Expression Recognition and the steps  involved in the FER system, such as face detection,  extraction, and expression categorization. Everything, like  any new technology, has advantages and drawbacks. When  utilizing the AFEW dataset, the FER system also has a  problem with accuracy, since the accuracy is only 50%.  With the advancement of technology, this precision will  increase in the future. As a result, the FER system has a  promising future.
Keywords: Algorithm; Detection; Extraction; Face Expression Recognition (FER); System